Comparison of Pharyngeal Airway between Mandibular Setback Surgery Patients (Skeletal Class III) and Nonsurgery Patients (Skeletal Classes I and II). (17th March 2019) - Cheng, Jung-Hsuan; Chen, Chun-Ming; Chen, Ping-Ho; Chou, Szu-Ting; Pan, Chin-Yun; Tseng, Yu-Chuan
Abstract : Purpose . We investigated the pharyngeal airway dimensions and their correlations in patients who underwent mandibular setback surgery versus those who did not. Materials and Methods . One hundred and sixty cephalometric radiographs (120 patients) were obtained from patients with three skeletal malocclusion classifications: Class I and Class II in the nonsurgery group and Class III in the surgery group (preoperative and postoperative cephalograms). The following dimensions were measured: nasopharyngeal airway (NOP), uvulopharyngeal airway (UOP), shortest distance from the posterior tongue to the pharyngeal wall (TOP), and distance from the epiglottis to the pharyngeal wall (EOP). Paired t test, one-way analysis of variance, and Pearson correlation coefficients were used for statistical analysis. Results . Preoperatively, UOP and TOP of skeletal Class III patients (15.2 mm and 16.6 mm) were significantly larger than those of skeletal Class II (11.5 mm and 12 mm) and Class II (12.3 mm and 12.9 mm) patients, respectively. No differences were observed in EOP between the three skeletal patterns. The hyoid bone of Class III patients was significantly anterior to that of Class I/II patients. Furthermore, UOP had a moderate negative correlation with soft palate length. Postoperatively, no significant difference (UOP, TOP, EOP, soft palate width, and hyoid bone) was found between the skeletal classes. Conclusion . Preoperatively, UOP and TOP of skeletal Class III patients were significantly wider than those of skeletal Class I/II patients. Pre- and postoperatively, EOP did not exhibit significant differences among the three skeletal classifications. No differences were found in all postoperative pharyngeal airway dimensions between Class III patients and nonsurgery patients (Class I and Class II).